Electrochemically Exfoliated Phosphorene–Graphene Hybrid for Sodium‐Ion Batteries. Issue 2 (15th October 2018) - Shuai, Honglei; Ge, Peng; Hong, Wanwan; Li, Sijie; Hu, Jiugang; Hou, Hongshuai; Zou, Guoqiang; Ji, Xiaobo
Abstract: Black phosphorus, an attractive anode material for sodium‐ion batteries (SIBs), has aroused grand attention because of its high theoretical capacity. Nevertheless, its practical exploration is limited by large volume swelling, followed by rapid capacity decaying. Herein, both large‐area few‐layer phosphorene and low‐defect graphene are obtained by electrochemical exfoliation. The sandwich‐structured phosphorene–graphene hybrid with the simultaneous introduction of PC and POC bonds through chemical activation is employed to heighten the performance of SIBs, leading to a high specific capacity of 2311 mA h g −1 (based on the mass of phosphorene) at 0.1 A g −1 with a capacity retention of 83.9% after 100 loops, which can be ascribed to the flexible space of graphene layers that alleviates the volumetric expansion of phosphorene. Moreover, the stable chemical bonds as the bridge for electrons transferring can immobilize phosphorene and protect phosphorene from cracking during the sodiation/desodiation process. Expectedly, the anode exhibits excellent cycle performance of 200 loops with retained capacities of 1582.6 and 1120.6 mA h g −1 at 1 and 5 A g −1, respectively. Therefore, this electrochemical approach provides a guide for the preparation of other sandwiched 2D materials, which can be applied in high‐performance energy‐storage devices. Abstract : A sandwich structured phosphorene–graphene hybrid is well‐designed through chemical activation with electrochemically exfoliated phosphorene and graphene. Simultaneously, the formation of PC and POC bonds can protect phosphorene from cracking, and graphene offers an elastic buffer to accommodate the volumetric expansion of phosphorene. This work may provide a guide for the future design of high‐performance anode material for sodium‐ion batteries (SIBs).